Optimization of Angoumois Grain Moth (Sitotroga cerealella Olivier) Infestation in Stored Grains as Influenced by Some Botanical Powders - Mahmudul Hasan; Kazi Shahanara Ahmed; Nayan Chandra Howlader; Md. Mahfuzul Hasan; Mita Saha Puja; Most. Safia Farhana; Maruf Hasan Nikson (Turkish Journal of Agriculture: Food Science and Technology)
The Angoumois grain moth, Sitotroga cerealella Olivier is predominantly a devasting infested stored grain pest of cereals, whose development proceeds within a single grain of infested cereals. Investigating greener alternatives to widely used chemical control techniques is crucial because synthetic chemicals pose risks to public health and the environment.  This investigation was carried out for developing the ecofriendly control management of the Angoumois grain moth in stored cereals through utilizing four botanical powders and one insecticide, wood ash (1 gm), and a single synthetic insecticide (Carbaryl) (0.25mg), neem (1 gm), Korobi (1 gm), Bishkatali (1 gm) and Datura (1 gm) treatments against untreated control in Completely Randomized Design (CRD). It was revealed that Neem (Azadiracta indica) powder at 1 g/100 g seed performed excellently, resulting in minimization of adult mortality percent, adult emergence, grain weight loss, and number of holes per ten seeds. The maximum percent of germination was noted in bishkathali (Persicaria lapathifolia) powder at 1 g/100 g seed, and moreover, bishkathali powder functions more effectively for limiting infestation percent. Therefore, the botanical neem and bishkathali powder at 2 g/100 g seed rate is the better alternative of carbaryl at 0.5 g/100 g rate, and it could be suggested for Angoumois grain moth management at storage.